HbA1C and Cancer Risk in Patients with Type 2 Diabetes – A Nationwide Population-Based Prospective Cohort Study in Sweden - Miao Jonasson, Junmei; Cederholm, Jan; Eliasson, Björn; Zethelius, Björn; Eeg-Olofsson, Katarina; Gudbjörnsdottir, Soffia (PLOS ONE, 2012)
Background Diabetes is associated with increased cancer risk. The underlying mechanisms remain unclear. Hyperglycemia might be one risk factor. HbA1c is an indicator of the blood glucose level over the latest 1 to 3 months. This study aimed to investigate association between HbA1c level and cancer risks in patients with type 2 diabetes based on real life situations. Methods This is a cohort study on 25,476 patients with type 2 diabetes registered in the Swedish National Diabetes Register from 1997–1999 and followed until 2009. Follow-up for cancer was accomplished through register linkage. We calculated incidences of and hazard ratios (HR) for cancer in groups categorized by HbA1c ≤58 mmol/mol (7.5%) versus >58 mmol/mol, by quartiles of HbA1c, and by HbA1c continuously at Cox regression, with covariance adjustment for age, sex, diabetes duration, smoking and insulin treatment, or adjusting with a propensity score. Results Comparing HbA1c >58 mmol/mol with ≤58 mmol/mol, adjusted HR for all cancer was 1.02 [95% CI 0.95–1.10] using baseline HbA1c, and 1.04 [95% CI 0.97–1.12] using updated mean HbA1c, and HRs were all non-significant for specific cancers of gastrointestinal, kidney and urinary organs, respiratory organs, female genital organs, breast or prostate. Similarly, no increased risks of all cancer or the specific types of cancer were found with higher quartiles of baseline or updated mean HbA1c, compared to the lowest quartile. HR for all cancer was 1.01 [0.98–1.04] per 1%-unit increase in HbA1c used as a continuous variable, with non-significant HRs also for the specific types of cancer per unit increase in HbA1c. Conclusions In this study there were no associations between HbA1c and risks for all cancers or specific types of cancer in patients with type 2 diabetes.